‘Gay Strangers’: Reflections on Decadence and the Decadent Poetics of A. Mary F. Robinson - Ana Parejo Vadillo (Cahiers Victoriens et Edouardiens)
This paper reflects on what it means to write decadent poetry with a Latin complexion. It begins by revisiting some of the debates surrounding the return of Latin to fin-de-siècle writing to highlight that writers like Alice Meynell and A. Mary F. Robinson (women of style—as opposed to Walter Pater’s man of style) were part of these debates. It then moves on to consider the possibility of another fin-de-siècle poetic paradigm resulting from this return to Latin. It examines the idea of composition as a form of composure, and examines in this context the decadent poetics of A. Mary F. Robinson. It offers a reading of the philological poetics of her 1893 volume of poems, Retrospect, as a reflection of a poet in exile concerned with the question of how language composes feeling.